Politik Lokal Calon anggota badan Perwakilan Desa di Desa Sardonoharjo - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The promulgation of the Act No. 22 of 1999 makes the Act No. 5 of 1974 and the Act No. 5 of 1979 legally invalid. The consequence of this change is the shift of the role and function of the governing bodies in the village level. Based on the Act 22 of 1999, one of the village governing body, namely Village Deliberation Board has to be replaced by the Village Representative Board Thus, the election process of the members of the Village Representative Board constitutes a national agenda, which has to be performed by village. The main goal of this research is to find out the description of various local politics used by the candidates in order to win the membership of the Village Representative Board in Sardonoharjo village. Data collection for this research was carried out through in-dept interview, participatory observation and library study. The location of the research, namely Sardonoharjo Village in Sub-district of Ngaglik, Sleman Regency of Yogyakarta Province was chosen through purposive sampling technique. Respondents of this research were 11 members of the Board, S failed candidates, Head of the Board Committee Election, Board Secretary, Village Head, Former Head of the Village Deliberation Board, Sub-Village Head, a leading figure in the village, and two key informants. Data collected from library and the field were qualitatively analyzed. The result of this research indicated that in order to win the membership of the Village Representative Board, the candidates used various local politics such as inviting mass, doing campaign, reinforcing family networking, making success team, money politics, and political coalition.